The role of the firm in worker wage dispersion: an analysis of the Ghanaian manufacturing sector - Somdeep Chatterjee (IZA Journal of Labor & Development, 2016)
This paper uses a linked employer-employee dataset from the Ghanaian manufacturing sector to analyze earnings dispersion in Ghana from 1992 to 2003, a period post extensive economic reforms. I find that variance of earnings increased from 1992 to 1998 and decreased thereafter, resembling an inverted u-shaped relationship. I use analysis of variance and variance decomposition approaches to understand the underlying factors that led to such a pattern in earnings inequality. I find that between-firm factors explain this pattern more than within-firm factors. I also find that the mean earnings gap between workers above and below the 90th percentile of income distribution can explain the majority of the initial surge in inequality (61 %) but only explains a very small fraction of the eventual decline (9 %). I run OLS regressions similar to Mincerian equations and decompose the variance components to find that the decline in earnings inequality is consistent with decline in variance of firm-level earnings whereas variance of predicted wage from worker characteristics have increased. I also find suggestive evidence of changing patterns of worker-firm sorting which contributes to the decline in inequality. These patterns however only hold up for private domestic firms and not for foreign-owned firms.
Keywords: J31; O15; 330; Wage dispersion; Inequality; Firm effects; Analysis of variance; Variance decomposition